PEMETAAN SEBARAN PENYAKIT DI WILAYAH KABUPATEN PROBOLINGGO DENGAN GOOGLE API - Sulistiyanto Sulistiyanto (Jurnal Teknologi Informasi dan Terapan, 2019)
There are three types of disease that generally affects the population Probolinggo district include Dengue Hemorrhagic Fever (DHF), diarrhea and tuberculosis, diseases that often lead to extraordinary events in Indonesia. All three of these diseases can spread rapidly and cause death within a short time. Prediction of the occurrence of Dengue Hemorrhagic Fever (DHF), diarrhea and tuberculosis in Probolinggo need to be made in the form of web-based GIS program. This system helps the government and the public to know the number of patients, in an area, such as an image display data in map form. The research method used is the method of data collection consisted of interviews, observation, and literature. While the development of the system used on the Web GIS uses waterfall method. The design of the map is displayed using the Google Maps API, software used in building this cycle is PHP. Results of this information media creation is "Mapping the Distribution of Disease in Probolinggo regency with the Google API" that can provide information to the community and the government to obtain information about the distribution of disease in Probolinggo through the Internet. As well as easy to use and can be accessed anywhere and anytime as long as there is internet network.